Focus of Research on Leadership in Islamic Education: Bibliometric Analysis - Fadli Agus Triansyah; Suwatno Suwatno; Eeng Ahman; Nurhoiriyah Nurhoiriyah; Yusupov Komaliddin Bakhtiyor Ugli (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
Leadership is not only about ordering or giving instructions but also involves motivating, inspiring, and influencing others to achieve common goals. Leadership can occur in a variety of fields, including business, politics, and education, and plays a critical role in the success of an organization or community. This research aims to identify publications related to leadership in Islamic education and describe the characteristics of this research. The bibliometric analysis method was used in this study. The research results show that publications about leadership in Islamic schools have increased yearly from 2019 to 2023—meanwhile, the largest number of documents come from Indonesian authors. Proceedings of the ICECRS hold the top position as an institution or publisher with the most four documents. In contrast, the author with the most citations is Firman-Mansir, with a total of 3 published documents and eight citations, followed by the writer Eugenie A Samier with a total of 3 and 5 citations of published papers and followed by writer Fitriyah with a total of 3 published documents and two citations. Keywords that appear a lot in joint events are Education, Islam, Institution, Approach, Leader, Development, Activity, Quality, Teacher and Problem. The new theme keywords are Strategy, Community, Skill, Creativity, Facility, Decision, Generation, Innovation, and Prophetic Leadership. Therefore, these new themes can become new material for further research that addresses this field.